The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution V. Family Andrenidae, genus Andrena Fabricius, 1775, species described by E. Eversmann - Astafurova, Yulia V.; Proshchalykin, Maxim Yu.; Sidorov, Dmitry A. (Zootaxa, 2022)
The type specimens for names of bee taxa in the genus Andrena Fabricius, 1775 described by E. Eversmann and which are deposited in the Zoological Institute, Russian Academy of Sciences (St. Petersburg) are reviewed. Primary types of 18 taxa are illustrated and detailed information is provided. New synonymy is established for three species: Andrena fallax Eversmann, 1852 (=A. ispida Warncke, 1965, syn. nov.); A. assimilis Radoszkowski, 1876 (=A. gravida Eversmann, 1852, nec A. gravida Imhoff, 1832, syn. nov.); A. nigriceps (Kirby, 1802) (=A. nigrifrons Eversmann, 1852, syn. nov.). Based on the lectotype studying we consider Andrena fulva Eversmann, 1852 (nec A. fulva Müller, 1766) to be a junior synonym of A. (Taeniandrena) eversmanniana Osytshnjuk, 1994, stat. rev., not A. (Margandrena) marginata Fabricius, 1776, as opposed to Gusenleitner & Schwarz (2002). Corrections on lectotype data are provided for four taxa: Andrena ambigua Eversmann, 1852, A. consobrina Eversmann, 1852, A. fulvitarsis Eversmann, 1852, and A. scita Eversmann, 1852.